Pengaruh Penggunaan Aplikasi Gojek Terhadap Perilaku Mahasiswa Universitas - Eryc Eryc (Universitas Bandar Lampung (UBL), 2022)
Currently, businesses engaged in online transportation are growing rapidly. The company really helps the community from doing daily activities to entertainment. The user only uses the phone, and the user can handle everything in one application. This software has many features from online food delivery, drug delivery, transportation, and so on. Corporate marketing is widespread and many people are free to use it, from high school students to adults. This research is to know the students' behavioral intentions. It is necessary to know the factors that attract users to Gojek application. The factors themselves are Performance Expectancy, Social Influence, Effort Expectancy, Facilitating Condition, Price Value, Hedonic Motivation, Habit to Behavioral Intention, and Use Behavior based on Unified Theory of Acceptance and Use of Technology (UTAUT 2) as a theoretical framework using Smart PLS -3, namely the acceptance of technology in the context of consumer use. Based on the results of research with 160 respondents among students in the city of Batam, there are 3 relationships that have positive and significant values. Variables that affect Behavioral Intention are Habit and Hedonic Motivation. then the variable that has an effect on Use Behavior is Behavioral Intention while the other variables have no significant effect. The results of the Coefficient of Determination (R2) test, the factors above have an effect on Behavioral Intention of 60.4% and the effect of Use Behavior is 54.4%.